Hankiss János (1893–1959) professzor, tudományszervező és -népszerűsítő - Gorilovics, Tivadar (Gerundium, 2011)
Professor János Hankiss (1893–1959), Organizer and Popularizer of Scholarship. The lecture from which the written essay has evolved, memorializes János Hankiss, the internationally reputed Professor of French of the University of Debrecen by recalling the most significant stages and achievements of his professional teaching and research career, also including his attainments in the organization of scholarship. He started his academic career at the University of Debrecen in 1920. In the distinguished community of his peers who taught at our university between the two world wars, János Hankiss undubitably belonged to the top professionals. If a university’s academic rank is determined not only by its local or national prestige but also by its international recognition and appreciation, then in this latter frame of reference it was perhaps Professor Hankiss who did most to put Debrecen on the map for Europe and beyond. Indeed, he would share his knowledge not only within the confines of the University: he was a popularizer of scholarship and of the literary culture who was ready to move beyond the narrow limits of his immediate professional field and to address a larger audience. Besides, his name is also associated with the still extant quarterly periodical Debreceni Szemle [Debrecen Review] and Debrecen University’s International Summer School.